Governing body priorities in tennis science research - Miller, S. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this paper is to describe key projects developed by the ITF Technical Centre to understand the characteristics of tennis equipment and their effects on the Rules of Tennis. These projects involve the ball (spin and aerodynamics), racket power and surface (friction). While each of these projects provides valuable information, it is not as useful in isolation than it is together, when an overall view on the combined effects of different combinations of tennis equipment on the nature of tennis can be established.